Teachers’ Pay for Performance in the Long-Run: The Dynamic Pattern of Treatment Effects on Students’ Educational and Labour Market Outcomes in Adulthood - Lavy, Victor (Review of Economic Studies, 2020)
Abstract This article examines the dynamic effects of a teachers’ pay for performance experiment on long-term outcomes at adulthood. The program led to a gradual increase in university education of the treated high school students, reaching an increase of 0.25 years of schooling by age 28–30. The effects on employment and earnings were initially negative, coinciding with a higher rate of enrolment in university, but became positive and significant with time. These gains are largely mediated by the positive effect of the program on several high school outcomes, including quantitative and qualitative gains in the high-stakes matriculation exams.